Performance of hybrid rice grown from separated tillers (Journal of the Bangladesh Agricultural University, 2019)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during July to November 2016 to investigate the performance of separated tillers of hybrid rice variety Dhani Gold. The experiment comprised three times of tiller transplantation viz. 3, 4 and 5 week aged tiller seedlings and four levels of number of tiller seedlings transplanted hill-1 viz. 2, 3, 4 and 5 tiller seedlings hill-1 laid out in a split plot design with 3 replications. The highest plant height was obtained when 3-week aged tiller seedlings were transplanted at the rate of 3 tiller seedlings hill-1. The highest number of total tillers hill-1 and number of effective tillers hill-1 were found when 3-week aged tiller seedlings were transplanted with 5 tiller seedlings hill-1. The highest grains panicle-1 was obtained when 4-week aged tiller seedlings were transplanted with 5 tiller seedlings hill-1. The highest grain yield was found when 3-week aged tiller seedlings were transplanted with 5 tiller seedlings hill-1. The lowest grain yield was found when 5-week aged tiller seedlings were transplanted with 2 tiller seedlings hill-1 in hybrid rice variety Dhani Gold. Based on the findings of the present study it may be concluded that 3-week old tiller seedlings of Dhani Gold should be transplanted at the rate of 4 or 5 tiller seedlings hill-1 for higher yield. Thus present study confirms the potentiality of growing hybrid rice from separated tillers in case of unavailability of seedlings or to minimize the seed cost of high value hybrid rice seeds.J Bangladesh Agril Univ 17(4): 507–513, 2019